Effect of performance feedback during 6 weeks of velocity based squat jump training - Randell, A.; Cronin, J.; Keogh, J.; Gill, N.; Pedersen, M. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study investigated the effect of instantaneous performance feedback (peak velocity) provided after each repetition of squat jump exercises in 13 professional rugby players. Players were randomly assigned to a feedback or non feedback group and completed three training sessions per week for six weeks. The relative magnitude (effect size) of the training effects for all performance tests were found to be small, except for 30m sprint which was moderate. The use of feedback was found to be possibly beneficial to increasing vertical jump, 10m and 20m sprint, likely to be beneficial to increasing horizontal jump and almost certainly beneficial to increasing 30m sprint. It is suggested that the provision of instantaneous feedback on movement velocity during resistance training sessions provides a greater potential for adaptation and larger training effects.